Creativity in the Person: Contemporary Perspectives (LEARNing Landscapes, 2012)
All individuals, working alone or in collaboration with others, have creative characteristics, but activate and apply them in varied ways, at different times, and in response to differing tasks and conditions. A shift from asking, "How creative are you?" to the challenging question, "How are you creative?" moves us beyond looking at level of creativity ("high, average, or low") and to consider style of creativity (varied ways of expressing and applying creativity). Understanding each student’s unique creative strengths enables educators to differentiate learning and instruction effectively for creativity and innovation as well as for other important educational outcomes.
Keywords: creativity; style; learning; instruction